Prevalence of iron overload in patients with chronic kidney disease on peritoneal dialysis: A scoping review - Abdulqadir J. Nashwan (11659453) (2024)
Background and Aims Chronic kidney disease (CKD) patients undergoing peritoneal dialysis (PD) are susceptible to complications, including iron overload, which can significantly impact their prognosis and overall health. This scoping review aimed to study the prevalence and implications of iron overload in CKD patients undergoing PD. Methods A comprehensive search was conducted across five databases, leading to the selection of 18 papers for in‐depth analysis. These studies collectively involved 381 PD patients, 60.3% were males. Results No consensus was reached regarding the exact diagnostic cutoff for iron overload. The investigations revealed four main aspects: (1) Seven papers identified various factors contributing to iron overload, emphasizing the role of different iron supplements and magnetic resonance imaging's capability to diagnose iron accumulation in organs; (2) Iron overload in young patients was found to hinder growth; (3) Six studies highlighted the adverse effects of iron overload, with cardiac issues being the most significant; (4) Three studies demonstrated the efficacy of iron‐chelating agents, Deferoxamine and Deferasirox, in treating iron overload patients undergoing PD. Overall, the estimated prevalence of liver iron overload in CKD patients on PD ranges from approximately 10% to 28.6%, which is far lower than the prevalence of 75% elegantly shown in HD patients. Conclusion While iron overload was a significant concern for CKD patients undergoing PD in the past, it is less common in the current era due to advancements in treatments, such as erythropoiesis‐stimulating agents. Treatment with specific chelation agents has proven beneficial, but there is also a risk of adverse effects, necessitating meticulous monitoring and timely intervention. Other Information Published in: Health Science Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/hsr2.2255